2021
DOI: 10.3390/atmos12040503
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Thermal Microcosms at the Forest Floor—A Case Study of a Temperate Forest

Abstract: With the expected changes in summer weather due to global warming, knowledge of the microclimatic variability at the forest floor dramatically increased in importance for silviculture, wildfire management and biodiversity issues. Thus, during the warm season in 2014, thermal aspects within a heterogeneous forest were recorded at nine sites and compared to data from a nearby weather station. It was found that soil (−5 cm) and near-surface (0–2 cm) temperatures under shaded conditions stayed remarkably cooler th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Likewise, a threshold in canopy cover has been proposed, below which buffering properties in temperate forests largely would decrease [30,70]. In this context, Boehnke et al (2021) [14] carried out a detailed study within a flat coniferous forest and demonstrated that the cooling effect of canopy shading resulted in comparably cool conditions in the forest soil and at the surface only in highly shaded sites, while the surface temperature reached considerably higher temperatures than nearby areas outside. Our study demonstrated that not only was canopy closure relevant for the refugial capacity but also the variability of tree heights (Elev.…”
Section: Refugial Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, a threshold in canopy cover has been proposed, below which buffering properties in temperate forests largely would decrease [30,70]. In this context, Boehnke et al (2021) [14] carried out a detailed study within a flat coniferous forest and demonstrated that the cooling effect of canopy shading resulted in comparably cool conditions in the forest soil and at the surface only in highly shaded sites, while the surface temperature reached considerably higher temperatures than nearby areas outside. Our study demonstrated that not only was canopy closure relevant for the refugial capacity but also the variability of tree heights (Elev.…”
Section: Refugial Capacitymentioning
confidence: 99%
“…Topographically complex areas like mountains include many climate-forcing factors at a fine spatial resolution [10,11] such as terrain features that reduce solar radiation (e.g., slope, aspect) and landforms that favor humidity stability or accumulation of cold air (e.g., canyons) (e.g., [12,13]). In addition, mountains are covered by different patches of vegetation, and living under the tree canopy means experiencing damped extreme temperatures (lower maximums and higher minimums), as well as lower direct sunlight and wind speed [14,15]. However, microclimatic conditions under the canopy in terms of temperature, light, and humidity will depend on the forest structure (tree density, canopy height) and topographic position (e.g., [16][17][18]).…”
Section: Introductionmentioning
confidence: 99%
“…The metabolism of trees, for example, binds CO 2 (function → ESS climate protection) as well as part of the incoming solar radiation, which thus does not contribute to local warming. The water evaporating through the leaves cools the surrounding air, and the shade provided by the leaves cools both the ground beneath the tree, i.e., the living space for people outside and-if the tree shades a building-also the building inside (function → ESS climate adaptation) [40][41][42][43]. All in all, the described functions lead to the UES "microclimate regulation" or, more specifically, "local cooling", which in turn contributes to the maintenance of human well-being in the urban environment during summer heat (right side of the cascade: contribution to human well-being, "benefits").…”
Section: A General Approach To Link Urban Space and Greenery With Eco...mentioning
confidence: 99%
“…Urban trees significantly mitigate the heating of the ground (and building surfaces) in summer due to shading of the canopy [43,54,60,61]. The canopy diameter provides a quantitative estimate of the tree cover and its minimum shading potential ("crown footprint") [60].…”
Section: Shadingmentioning
confidence: 99%
“…Depending on the vegetation cover, the microclimatic variability can even exceed the variability of the macroclimate (Zellweger et al, 2020). Although in deciduous forests with completely closed vegetation cover, less than 10% of direct beam and diffuse radiation reaches the forest floor, they still experience diurnal fluctuations in nearground temperature (Reifsnyder et al, 1971;Hutchison and Matt, 1977;Boehnke, 2021). Further, the loss of vegetation canopy has increased with climate warming and is likely to increase further due to enhanced disturbances and tree die-off due to climate change (Schelhaas et al, 2003;Seidl et al, 2014).…”
Section: Introductionmentioning
confidence: 99%